1988
DOI: 10.1093/ajcn/48.6.1375
|View full text |Cite
|
Sign up to set email alerts
|

Studies in human lactation: milk volumes in lactating women during the onset of lactation and full lactation.

Abstract: After validation of test-weighing procedures milk volumes produced by 13 multiparous Caucasian women were followed longitudinally through the first year of lactation. All practiced exclusive breast-feeding for at least 5 mo. Milk transfer to the infant was low on days 1 and 2 and increased rapidly to 498 +/- 129 g/d (means +/- SD) on day 5 and then more slowly to 753 +/- 89 g/d during months 3-5. There was a characteristic milk volume for each mother-infant pair that was significantly related neither to milk y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
226
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(246 citation statements)
references
References 32 publications
16
226
3
1
Order By: Relevance
“…Milk volume obtained from these mothers is less than those previously reported for mothers of term infants, suggesting that mothers of VLBW infants may produce less breast milk than mothers of term infants in the first 7 days following delivery. 31,35,36 Mothers in the early initiation group had a significantly shorter time to onset of lactogenesis stage II than mothers in the late initiation group. This suggests that milk expression within the first hour following delivery may result in an earlier onset of lactogenesis stage II.…”
Section: Discussionmentioning
confidence: 97%
“…Milk volume obtained from these mothers is less than those previously reported for mothers of term infants, suggesting that mothers of VLBW infants may produce less breast milk than mothers of term infants in the first 7 days following delivery. 31,35,36 Mothers in the early initiation group had a significantly shorter time to onset of lactogenesis stage II than mothers in the late initiation group. This suggests that milk expression within the first hour following delivery may result in an earlier onset of lactogenesis stage II.…”
Section: Discussionmentioning
confidence: 97%
“…7,8,10,17,20 However, studies examining milk intake and infant weight gain in exclusively breastfed infants have demonstrated that less than 5% of mothers are actually unable to produce adequate milk to meet their infant's nutritional needs in the first four months of life. 18,[20][21][22][23] Young mothers (<25 years) and primiparous mothers were more likely to cite "not enough breast milk" as a reason for cessation, suggesting that perceptions of low milk supply may be linked to a lack of knowledge about breastfeeding or lack of previous breastfeeding experience. A recent Cochrane review of support for breastfeeding mothers with healthy term babies found that support from both professionals and lay supporters increased the duration; however, support offered reactively, which was initiated only after women sought out contact instead of on an ongoing, scheduled basis, was not effective.…”
Section: Discussionmentioning
confidence: 99%
“…Individual milk volume varies considerably among women, with typical production ranging from 550 to 850 mL per day (Neville et al, 1988). Milk supply is determined by the flow of milk through the mammary gland (Akers, 2002).…”
Section: Sources Of Variation In Human Milkmentioning
confidence: 99%